"SCIENCE, " "RELIGION, " AND "SCIENCE‐AND‐RELIGION" IN THE LATE OTTOMAN EMPIRE: with Jaume Navarro and Kostas Tampakis, "Science and Religion in Nineteenth‐Century Europe: Non‐Anglo‐American Perspectives"; M. Alper Yalçinkaya, "'Science, ' 'Religion, ' and 'Science‐and‐Religion' in the Late Ottoman Empire"; Kostas Tampakis, "High Science and Natural Science: Greek Theologians and the Science and Religion Interactions (1832–1910)"; Agustín Ceba Herrero and Joan March Noguera, "'Serving God, Fatherland, and Language': Alcover, Catalan, and Science"; Jaume Navarro, "Draper in Spain: The Conflicting Circulation of the Conflict Thesis"; and Neil Tarrant, "Science, Religion, and Italy's Seventeenth Century Decline: From Francesco de Sanctis to Benedetto Croce.". Issue 4 (13th November 2019) - Yalçinkaya, M. Alper
Abstract: Many intellectuals wrote texts on the relations between Islam and science in the nineteenth‐century Ottoman Empire. These texts not only addressed the massive social and cultural changes the Empire was going through, but responded to European authors' claims about the extent to which Islam was compatible with the modern world. Focusing on several texts written in the second half of the nineteenth century by the influential Muslim Ottoman authors Namik Kemal, Ahmed Midhat, and Şemseddin Sami, this article shows the influence of these exigencies on arguments on Islam and science. In order to represent Islam as a respectable religion in harmony with science, these intellectuals defined a "pure Islam" that was a set of basic principles that could be found in the Qur'an. Rather than an embedded way of life, Islam in these texts was an objectified, delimitable entity that could be imagined as having relations with other entities, such as science.